Women in Concrete Poetry: 1959-1979 - Balgiu, Alex; de la Torre, Monica (Brooklyn : Primary Information, 2020)
It gathers work by over 40 writers and artists, including Lenora de Barros (Brazil), Mirella Bentivoglio (Italy), Amanda Berenguer (Uruguay), Suzanne Bernard (France), Tomaso Binga (Italy), Blanca Calparsoro (Spain), Paula Claire (UK), Betty Danon (Turkey), Mirtha Dermisache (Argentina), Ilse Garnier (France), Anna Bella Geiger (Brazil), Bohumila Grögerová (Czech Republic), Ana Hatherly (Portugal), Susan Howe (USA), Tamara Jankovic (Serbia), Annalies Klophaus (Germany), Barbara Kozlowska (Poland), Liliana Landi (Italy), Liliane Lijn (USA), Françoise Mairey (France), Giulia Niccolai (Italy), Jennifer Pike (UK), Giovanna Sandri (Italy), Mira Schendel (Brazil), Chima Sunada (Japan), Mary Ellen Solt (USA), Salette Tavares (Portugal), Colleen Thibaudeau (Canada), Rosmarie Waldrop (USA) and Ruth Wolf-Rehfeldt (Germany)
boek